Comparative Costs in the Worsted-Cloth Manufacture, American and Foreign - Cole, Arthur H. (Quarterly Journal of Economics, 1929)
Journal Article Comparative Costs in the Worsted-cloth Manufacture, American and Foreign Get access Arthur H. Cole Arthur H. Cole Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 43, Issue 3, May 1929, Pages 550–561, https://doi.org/10.2307/1885925 Published: 01 May 1929